Soil and artesian water reseach in the private sector of Poltava (dendropark area) - Іваницька, І. О.; Сененко, Н. Б.; Романович, І. С.; Санжаревська, О. І. (Scientific Progress & Innovations, 2012)
The results of the complex experimental research of soil samples and main physical–chemical characteristics of decentralized water supply selected in the center in Poltava (Dendropark area) are given. Analysis of influence of water-soluble soil component on this aquifer is conducted. The investigated water does not meet the physiological needs of the human body has been proved on the basis of results and comparison them with the requirements established by State Sanitary Regulations and Standard. Conclusions about regular control of soil and drinking water quality and improvement for using by population are drawn.